Melancholy Hues: The Futility of Green Growth and Degrowth, and the Inevitability of Societal Collapse - Wim Naudé (Institute of Labor Economics (IZA), 2023)
The economic expansion witnessed in the last 0,08% of modern human history is an anomalous event. It has been compared to a "rocket ship that took off five seconds ago, and nobody knows where it's going." This paper explores the destiny of this rocket ship. It shows that economic growth cannot continue indefinitely and critically reviews Green Growth and Degrowth as responses to planetary overshoot. It concludes that neither Green Growth nor Degrowth will stop overshoot. Moreover, Degrowth may worsen the environment, is a costly method to reduce carbon emissions, is a form of austerity for the working class, is redundant, and is politically infeasible. Finally, a third approach beyond Green Growth and Degrowth is outlined: acceptance of an inevitable societal collapse (as a feature, and not a bug, of complexity) and managing such a collapse to minimise harm, and to get rid of obsolete structures. This may lay the foundation for rebound growth, and a transition to a new kind of economy, which could be as qualitatively different from the current global economy as the industrial world differed from the hunter-gatherer world.
Keywords: O40; O33; D01; D64; 330; Green Growth; Degrowth; energy; ecology; development; collapse